The mediating role of self-efficacy in nursing students' initial clinical practice experience - Turan, Mensure; Cengiz, Zeliha (Elsevier Science Inc, 2025)
Background: Self-efficacy serves as a mediator between individual performance and knowledge, and is crucial in ensuring the delivery of appropriate nursing care in complex clinical scenarios. Consequently, it is imperative to ascertain the influence of self-efficacy levels on the assessment of nursing students' clinical performance. Aim: Examine the mechanisms through which stress experienced by nursing students in clinical setting affects their attitudes during their initial clinical practice experience, and to elucidate the role of clinical self-efficacy as a mediator in this process. Methods: This descriptive and correlational study was conducted with 169 first-year nursing students. The data analyses based on the Bootstrap method were performed using the SPSS and AMOS 24 program. Results: As a result of the analysis, the model was found to be significant, with 29% of the change in the students' attitude score towards clinical practice (,80=-0.171; R2=0.29) and 15% of the self-efficacy score explained by the stress they perceived (,81=-2.832; R2=0.15). Conclusion: The findings highlight the importance of self-efficacy in clinical practice education in the planning of educational programs. (c) 2025 Organization for Associate Degree Nursing. Published by Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Attitude; clinical self-efficacy; mediating model; perceived stress; student nurse